Cognition in Medical Practice - Ziółkowska-Juś, Anna (Sensus Historiae, 2023)
Integral cognition is an alternative to unilateral intellectual cognition. It does not focus on the intellect, but requires taking into account the senses, feelings, corporeality, as well as imagination and intuition hence it involves the whole person and his or her creative and direct interaction with the enviroments. Integral cognition is not a given. It requires education and is an important challenge today. The article demonstrates how to implement integral cognition into medical practice. Integral cognition in medical practice requires the involvement of aesthetic components. It is situated behind dichotomous division into irrational art and rational science.